Design and development of laboratory scale batch type device for debittering of bitter citrus juice. (2nd January 2023) - Gupta, Arun Kumar; Rather, Muzamil Ahmad; Mishra, Poonam
Abstract: Debittering of citrus juice has long been a stumbling challenge for the juice processing industries. The current debittering technique employs the adsorption of bitter compounds, which is reported to reduce a significant amount of vital nutrients, resulting in considerably lower antioxidant activity. Thus, in the present study, we are reporting a batch‐type laboratory‐scale debittering device using an interdigitated electrode (IDE), macroporous resin, and enzyme. Three different types of devices were developed. The first device was developed by adsorbing naringinase onto a macroporous resin and then being deposited on an IDE patterned printed circuit board (PCB) substrate. The second device was fabricated by the deposition of activated resin on IDE (an AR‐based device), while the third device was developed by depositing nonactivated resin on IDE (a NAR‐based device). The performance of the devices was evaluated by debittering the pomelo juice. It was observed that the device efficiently debitter 70–100 ml of juice in a batch manner. The juice was treated for 160 min at 60°C to determine the optimum time for a minimum level of naringin with the maximum retention of vital nutrients. A decreased level of naringin (53.06%) and increased naringenin content (16.19 ppm) were noticed with an increased time of exposure. Juice treated for 100 min had a significantly lower amount of naringin (39%), with maximum retention of vital nutrients. Contrary to this, juice treated with AR and NAR debittering devices reduced 32 and 19.65% of the naringin in 5 min with a maximum loss of bioactive compounds. The present study concludes that the fabricated debittering device reduced the bitterness up to a certain level with the minimum loss of other vital nutrients. Further study is needed to increase the handling capacity of juice and to study the storage stability of treated juice. Practical Application: Bitterness has long been a stumbling barrier to the commercial acceptance of citrus juice. There are limited studies that can monitor the elimination of bitter components from citrus juices. The current attempt investigates the development of a debittering device that can easily monitor the level of bitterness during the debittering process of bitter citrus fruit. The easy fabrication process, reusability of the proposed device, and cost factor could be an alternative way to boost the commerciality of underutilized citrus fruits. The developed technology has a strong potential to scale up, as the cost is minimal and the design of the setup is very simple. Abstract :